Magnesium Oxide Nanoparticles Reinforced Electrospun Alginate-Based Nanofibrous Scaffolds with Improved Physical Properties - R. T. De Silva; M. M. M. G. P. G. Mantilaka; K. L. Goh; S. P. Ratnayake; G. A. J. Amaratunga; K. M. Nalin de Silva (International Journal of Biomaterials)
Mechanically robust alginate-based nanofibrous scaffolds were successfully fabricated by electrospinning method to mimic the natural extracellular matrix structure which benefits development and regeneration of tissues. Alginate-based nanofibres were electrospun from an alginate/poly(vinyl alcohol) (PVA) polyelectrolyte complex. SEM images revealed the spinnability of the complex composite nanofibrous scaffolds, showing randomly oriented, ultrafine, and virtually defects-free alginate-based/MgO nanofibrous scaffolds. Here, it is shown that an alginate/PVA complex scaffold, blended with near-spherical MgO nanoparticles (⌀ 45 nm) at a predetermined concentration (10% (w/w)), is electrospinnable to produce a complex composite nanofibrous scaffold with enhanced mechanical stability. For the comparison purpose, chemically cross-linked electrospun alginate-based scaffolds were also fabricated. Tensile test to rupture revealed the significant differences in the tensile strength and elastic modulus among the alginate scaffolds, alginate/MgO scaffolds, and cross-linked alginate scaffolds (P<0.05). In contrast to cross-linked alginate scaffolds, alginate/MgO scaffolds yielded the highest tensile strength and elastic modulus while preserving the interfibre porosity of the scaffolds. According to the thermogravimetric analysis, MgO reinforced alginate nanofibrous scaffolds exhibited improved thermal stability. These novel alginate-based/MgO scaffolds are economical and versatile and may be further optimised for use as extracellular matrix substitutes for repair and regeneration of tissues.